Marketing Strategy Analysis Using SWOT And QSPM Methods In SMEs - Afif Shubbani; Akhmad Wasiur Rizqi; Hidayat Hidayat (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research focuses on one of the coffee-making SMEs. The many competitors in this business make it a challenge for companies to compete in marketing their product, namely coffee. From this, it is interesting for the author to make a study. This objective is made to determine the internal and external factors of the company and is used as input for the marketing strategy for the company. This study uses the SWOT and QSPM methods and uses primary and secondary data. The company's SWOT analysis results are in quadrant V. Based on the existing alternative strategies. It is analyzed using QSPM. The strategy chosen was to improve good relations with workers.